Enhancing communication and decision-making with AI - Das, Deepthi; Galety, Mohammad Gouse; Iwendi, Celestine; Natarajan, Arul Kumar; Shankar, Achyut (Advances in linguistics and communication studies (ALCS) book series., 2025)
"As artificial intelligence (AI) revolutionizes communication and decision-making, its impact on industries and daily life grows. The AI boom has created an exciting opportunity for leaders to optimize human interaction, streamline decisions, and boost productivity across various fields. To compete at the highest level in today's fast paced environments, understanding the potential of these technologies is essential. Enhancing Communication and Decision-Making With AI explores cutting edge possibilities for improvement in AI-driven collaboration, predictive analytics, and ethical considerations. These chapters provide practical applications and insights for integrating AI into communication and decision-making to create compelling communications material and drive consumer action. Covering topics such as social media influence, competitive advantage frontiers, and computational intelligence, this book is designed with professionals, researchers, and students in mind."--